Институциональный компонент экономической безопасности региона - Дмитриева, Марина Евгеньевна (Перспективы развития фундаментальных наук. Т. 5 : сборник научных трудов XVII Международной конференции студентов, аспирантов и молодых ученых, 21-24 апреля 2020 г., Россия, Томск)
As of this date the institutional component plays an important role in ensuring the economic security of the regions. The regulatory framework of the Russian Federation provides the regions with the opportunity to independently regulate certain types of activities through the creation of additional laws and other regulations. That it is to say, internationalization is manifested in this area, which provides predictability and orderliness of interaction between subjects.